Minimum Ischiopubic Ramus Width as a Single Metric for Sex Estimation: A Pilot Study - Mann, Robert W.; Ruengdit, Sittiporn; Rattanachet, Patara; Sangchay, Napakorn (Siriraj Medical Journal, 2025)
Objective: The present study assesses the effectiveness of the minimum width of the ischiopubic ramus as a single measurement for sex estimation. Materials and Methods: Visual and metrical examination of 135 known-identity male and female os coxae was investigated by measuring the minimum mediolateral width of the ischiopubic ramus, a novel and simple measurement of the narrowest part of the ischiopubic ramus. Results: The results revealed females typically have a narrow (“pinched”) ischiopubic ramus in comparison to males, with a statistically significant difference in the minimum mediolateral width of the ischiopubic ramus between sexes. Logistic regression, which delivered the best sex estimation model among traditional statistical analysis and machine learning approaches, provided an accuracy of 77.8%, a sensitivity of 83.33% and a specificity of 73.33% with a demarking point of 11.977 mm. Conclusion: Although the method yields moderate accuracy, the minimum width of the ischiopubic ramus provides a straightforward and practical approach that may assist in sex estimation when only a fragment of the ischiopubic ramus is available. Further validation using larger and more diverse samples is recommended to confirm its applicability.